2016
DOI: 10.1093/jxb/erw107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteomics of protein kinase SnRK1 regulated protein phosphorylation in Arabidopsis under submergence

Abstract: HighlightTo illustrate the hypoxia signal mediated by SnRK1.1, phosphoproteomics was used to identify not only the new SnRK1.1 putative targets related to submergence, but also to gain an insight into early hypoxia signalling events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 63 publications
2
111
0
Order By: Relevance
“…An Arabidopsis SnRK1.1 dominant-negative mutant showed lower tolerance to submergence (Cho et al, 2016). However, overexpression of the SnRK1 subfamily members KIN10 as well as the dominant-negative mutation in SnRK1.1 had no consequences on the starvation-dependent dampening of ADH expression (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…An Arabidopsis SnRK1.1 dominant-negative mutant showed lower tolerance to submergence (Cho et al, 2016). However, overexpression of the SnRK1 subfamily members KIN10 as well as the dominant-negative mutation in SnRK1.1 had no consequences on the starvation-dependent dampening of ADH expression (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…8A). We then tested the dominant-negative SnRK1.1 K48M line (Cho et al, 2016). The results showed that C starvation repressed ADH expression also in SnRK1.1 K48M , suggesting that the starvation-dependent effects of ADH expression are independent of SnrK1.1 (Fig.…”
Section: Sugar Starvation Dampens the Anaerobic Response Upstream Of mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, evidence for this scenario was provided recently by the finding that ABI4, a central TF involved in different chloroplast retrograde signaling pathways, was phosphorylated by the MAP kinase MPK6 in a Ca 2+ -dependent manner (Guo et al, 2016). Strikingly, MPK6 also was recently found to be regulated by SnRK1 under hypoxia conditions (Cho et al, 2016).…”
Section: Anterograde Signals To Organelles Via Phosphorylation Of Tramentioning
confidence: 99%
“…SnRK1 activation also is triggered by hypoxia, leading to suppression of mitochondrial aerobic respiration resulting in cellular energy deprivation (Im et al, 2014;Cho et al, 2016). Flooding stress or hypoxia leads to a reduced availability of O 2 as the final electron acceptor in the mitochondrial electron transport chain (mETC), causing a rapid decrease in the cellular ATP:ADP ratio (Bailey-Serres and Voesenek, 2008).…”
Section: Snrk1 In Metabolic and Hormone Signaling Under Stress Conditmentioning
confidence: 99%